Poliomyelitis vaccination status among children in the Federal Territory of Kuala Lumpur 2007 - AM Haliza; K Novia; N Odhayakumar; K Fadzilah; CK Chong; S Nirmal; S Balachandran; K Devan; K Gurpreet; A Hayati; YK Loe; P Senan (World Health Organization Regional Office for the Western Pacific, 2011)
Introduction: Polio vaccination rates remain low in certain regions of Malaysia. The Federal Territory of Kuala Lumpur (FTKL) reported coverage of only 29.3% in 2005 and 61.2% in 2006, despite a Department of Health campaign to provide free three-round immunizations. The estimated numbers of live births used to calculate these rates may have artificially lowered the reported coverage percentages.Methods: A descriptive, cross-sectional household survey was conducted throughout the FTKL in 2007 to assess the actual polio vaccination status of children aged 9 to 24 months. Minimum sample size was calculated and proportionately divided among the 11 FTKL parliamentary constituencies. Residential areas were then randomly selected for in-person interviews. We used the gathered information, verified by medical records, to calculate the actual vaccination coverage and to compare the rates determined by using estimated or registered live births for the region.Results: Of the 1713 study participants, 98.3% had completed their polio vaccination schedule. Only 21 children had been partially vaccinated, and nine children were completely unvaccinated. FTKL residents had 20 431 live births registered for 2006, as opposed to the official estimate of 28 400. When the registered value of live births was used to calculate vaccination coverage, the 2006 coverage increased (to 85.1%).Conclusion: Actual vaccination coverage in Kuala Lumpur was much higher than the estimated coverage previously reported, reflecting the expected success of the Department of Health immunization campaign. Estimated values of live births are insufficient to accurately determine vaccine status and should be avoided.